Momentum Politik dalam Pembangunan Komitmen Penanggulangan Bencana di Daerah - Ayu Wahyuningtyas (Jagratara: Journal of Disaster Research, 2023)
Approaching 2024, Indonesia will experience a process or momentum of changing heads of state and regional chiefs. Politically, if there is a new head of state, it is possible that there will be several legal policy reforms in the implementation of development, as well as disaster management policies. In terms of disaster events, natural disasters that occur during the implementation of political momentum can threaten the loss of political rights, damage to voter lists, disruption of supporting infrastructure, relocation of polling places (TPS), obstruction of logistics procurement and distribution channels, as well as delays in changing government. Thus, as a mitigation measure for disaster management during political momentum, synergy between Ministries/Institutions and Regional Governments is needed in dealing with natural disasters so that they do not disrupt political, legal and national security stability. Political momentum through simultaneous General Elections (Pemilu) and Regional Chiefs Elections (Pilkada) must be seen as momentum to emphasize the commitment of regional leaders to improving disaster management services to the community as well as realizing Indonesia as a Center of Excellence in Sustainable Resilience. Disaster issues must be given attention, including including disaster issues in the vision and mission in the Pilkada campaign and become a commitment of the elected Regional Chiefs